Taat Administrasi Perkara melalui Sosialisasi E Court oleh Pengadilan Negeri Kepanjen di Desa Tempursari Donomulyo - Anggi Pratiwi Agusta; Ninis; Khoirul Amin; Sinollah; Nur Hidayati (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2024)
The activities carried out in the Community Service journal are one of the efforts to implement the emergence of the Republic of Indonesia Supreme Court Regulation No. 7 of 2022 and Decree of the Chief Justice of the Supreme Court Number: 363/KMA/SK/XII/2022. Which can present new problems regarding the implementation of this e-court system which must reach the community and be implemented by all judicial institutions and legal interested parties, especially Malang Regency, East Java. In an effort to create a transparent and accountable judiciary, this activity aims to ensure that information about the E-Court system reaches the public and can increase administrative compliance in the implementation of justice, especially at the Kepanjen District Court. In this research we used a qualitative method that is analytical descriptive. The data sources we use are primary data from interviews with judges and officers of the Kepanjen Class 1B District Court, while we get secondary data sources from books and other readings related to research and tertiary data sources. Meanwhile, in data collection techniques we use observation, interviews and documentation. The final result of this activity is that we hope that the public can understand current technological developments, especially in the justice system such as e-Court.